Cancer Related Fears in Iranian Patients, a Survey from South East of Iran - Arbabi, Farshid; Shahbakhsh, Behnaz; Raghibi, Mahvash; Hemmati, Simin; Tajvidi, Mina (Reports of Radiotherapy and Oncology, 2023)
Introduction: Cancer is a chronic disease with an increasing incidence. Other than common complications of chronic diseases, the vague prognosis and early threat of cancers may induce tension and fears among patients. Such fears are of the main destructive aspects of cancer that make it a physically and emotionally weakening disease. Patients and Methods: In this study, we evaluated 111 patients with cancer who had been treated in the specialized cancer treatment center of Zahedan. They were asked to fill a questionnaire containing 44 questions about their fears and anxieties. We categorized the fears into social, individual, sexual, and disease related groups and these groups were analyzed according to the patients’ characteristics. Results: 26.1% of the patients were men and 73.9% were women with the mean ages of 45.9 and 44.9 years respectively. The majority of patients (79.3%) were married. T test analysis revealed that women experienced more social (P= 0.001) and personal fears (P= 0.015) than men. Married patients had more sexual fears than other groups (P= 0.001). One-way ANOVA for examining the effect of educational attainment, showed that the only variable with statistically significant difference among the means was the sexual fears (F (3, 108) =3.417, p=0.020). The patients with higher education levels had lower scores in sexual fears than other groups, meanwhile such type of the fears were more in the group of middle school education. Conclusion: Cancer is accompanied by different types of fears that affect the patient’s quality of life and satisfaction with treatment. It sees that detecting these fears and trying to resolve them, may help patients to have less stress during their life with cancer.